Investigation of the effect of chemotherapy on cytomegalovirus reactivity in patients with solid organ tumors - Demirel, Aslıhan; Nur Pilancı, Kezban; İnan, Neşe and İris, Nur Efe and Baygül, Arzu and Demir, Gökhan and Sönmez, Emine (The European Research Journal, 2021)
Objectives: Chemotherapy induces an immunosuppressive state in patients with solid organ tumors. Cytomegalovirus (CMV) reactivation as a result of immunosuppression causes a severe clinical manifestation. However, in this group, CMV infections developing due to reactivation were not adequately discussed in the literature. The aims of this study were to determine the incidence of CMV reactivation after chemotherapy, to evaluate the contribution of chemotherapy to reactivation, to determine the incidence of asymptomatic and symptomatic infections and to investigate the results of the treatment. Methods: A total of 93 patients with solid tumors were included in the study. Weekly blood samples were collected from the patients for three weeks before and after chemotherapy. Quantitative analysis of DNA was detected using CMV PCR kit (GeneProof CMV PCR kit, Bruno, Czech Republic). Diagnosis and treatment of patients were retrospectively reviewed. Results: Of the patients, 65.6% were female and 34.4% were male. The mean age was 55 ± 12 years. The most common cancer types among the patients were breast cancer in 45.2%, lung cancer in 15.1%, and colon cancer in 12.9%. The mean leukocyte count of the patients was 7,647/mm3. CMV DNA was not detected in any patient. According to this result, none of the patients had CMV reactivation after chemotherapy. Conclusions: In this study including patients with solid organ tumors with mild to moderate level of immunosuppression CMV DNA was not detected in any patient. Based on this finding no standard prophylaxis was required for CMV in this group of patients.